1991
DOI: 10.1182/blood.v78.6.1420.bloodjournal7861420
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of recombinant human interleukin-1 beta alone and in combination with myelosuppressive doses of 5-fluorouracil in patients with gastrointestinal cancer

Abstract: We studied escalating doses of recombinant human interleukin-1 beta (IL- 1 beta) alone and after a myelosuppressive dose of 5-fluorouracil (5- FU) in patients with gastrointestinal cancer. Transient neutropenia, monocytopenia, and lymphocytopenia were observed followed by a 1.3- to 6.0-fold (mean, 3.46-fold) dose-dependent neutrophil leukocytosis (P less than .00001) on the days of IL-1 beta administration. Increases in platelet counts were observed at a median of 14 days (range, 6 to 23) after IL-1 beta admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Trials of IL-1 in humans have demonstrated hypotension to be a limiting toxicity at doses of 0.1 1 pg per kg. 33 Other vascular effects of IL-1 administration include lactic acidosis, myocardial depression, vascular leak syndrome, and pulmonary congestion. The concomitant administration of TNF potentiates the systemic and vascular effects of IL-1.…”
Section: Resultsmentioning
confidence: 99%
“…Trials of IL-1 in humans have demonstrated hypotension to be a limiting toxicity at doses of 0.1 1 pg per kg. 33 Other vascular effects of IL-1 administration include lactic acidosis, myocardial depression, vascular leak syndrome, and pulmonary congestion. The concomitant administration of TNF potentiates the systemic and vascular effects of IL-1.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence suggest a role for IL-1 in platelet production. In vivo administration of IL-1bb to humans treated with chemotherapy (Crown et al, 1991(Crown et al, , 1993Redman et al, 1994;Rinehart et al, 1997) and to mice (Kimura et al, 1990;Dan et al, 1995) resulted not only in an improved neutrophil recovery but also in thrombocytosis. In patients with rheumatoid arthritis with marked thrombocytosis, increased plasma IL-1bb levels were found (Ertenli et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…IL-1 and TNFare major cytokines induced by endotoxin, and, if given before irradiation, can protect mice from doses of irradiation that would be fatal to untreated mice (Johnson et al, 1989;Neta & Oppenheim, 1991). However, the kinetics of haemopoietic reconstitution associated with IL-1 or TNFare different from that observed following AcSDKP because IL-1 or TNFinitiate a relatively prompt reconstitution of peripheral leucocytes, and does not affect the BM cellularity and numbers of progenitors (Crown et al, 1991). In addition, we determined the amount of endotoxin contaminated in AcSDKP, which was at a lower level (picogram quantities/mg protein) than is believed to have a biological effect on progenitor cells in vivo (Lord et al, 1992).…”
Section: Discussionmentioning
confidence: 98%